1998
DOI: 10.1002/(sici)1097-0215(19980130)75:3<362::aid-ijc6>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A and cancer prevention II: Comparison of the effects of retinol and β-carotene

Abstract: Former blue asbestos workers known to be at high risk of asbestos‐related diseases, particularly malignant mesothelioma and lung cancer, were enrolled in a chemo‐prevention program using vitamin A. Our aims were to compare rates of disease and death in subjects randomly assigned to β‐carotene or retinol. Subjects were assigned randomly to take 30 mg/day β‐carotene (512 subjects) or 25,000 IU/day retinol (512 subjects) and followed up through death and cancer registries from the start of the study in June 1990 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…For the residents' cohort, the following public records were searched (with the percentage of people they identified in parentheses): state primary school records (22%), general practitioner and Wittenoom hospital records (20%), the state Electoral Roll for the Pilbara region (12%), questionnaires sent to former Australian Blue Asbestos workers (14%), and participants in a cancer prevention program (18%; refs. 24,25). Table 1 shows in detail the establishment of the residents' cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the residents' cohort, the following public records were searched (with the percentage of people they identified in parentheses): state primary school records (22%), general practitioner and Wittenoom hospital records (20%), the state Electoral Roll for the Pilbara region (12%), questionnaires sent to former Australian Blue Asbestos workers (14%), and participants in a cancer prevention program (18%; refs. 24,25). Table 1 shows in detail the establishment of the residents' cohort.…”
Section: Methodsmentioning
confidence: 99%
“…All former residents traced to an address in Australia (n = 3,244, 64%) were sent a questionnaire in 1993, except 641 (13%), who were participating in the cancer prevention program and on whom the information was already available (24,25). The questionnaire ascertained their asbestos exposure experience including place and dates of residence at Wittenoom, whether they lived with and/or washed the clothes of an Australian Blue Asbestos worker, as well as demographic characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…A reliability study was conducted within a randomized clinical trial (the Vitamin A Program) which was designed to examine the efficacy of beta carotene and retinol (preformed vitamin A) supplements in reducing the risk of lung cancer, mesothelioma and possibly other malignancies after asbestos exposure 11 . Participants for the Vitamin A Program n 2769 were recruited from two large cohorts of former workers and residents of an asbestos mining and milling town in Western Australia 12 .…”
Section: Study Subjectsmentioning
confidence: 99%
“…In Australian study where 1,024 asbestos workers were enrolled in, the subjects were randomized to either β-carotene or retinol groups (De Klerk et al, 1998). After the follow-up period, no difference in lung cancer incidence was found, but the authors found that daily retinol was associated with lower rate of mesothelioma in crocidolite-exposed individuals, compared with daily β-carotene, which seemed to have no significant effect.…”
Section: Discussionmentioning
confidence: 99%